Vibration Analysis of the Steam Turbine Shafting Caused by Steam flow - Ge Li-juan; Zhang Chun-hui; Hao Min; Zhang Yong (Institute of Advanced Engineering and Science, 2013)
This thesis analyzes vibration test signal of TUOKETUO Power Plant 600 MW steam turbine unit through vibration monitoring and signal analysis on the basis of TN8000 Steam Turbine Vibration Analysis Software. Fault characteristics which is raised by Steam Flow Excitations is reproduced by acceleration constant speed test and load test. Steam flow mechanism of excitation caused by vibration fault and fault-sensitive parameter are analyzed, measures reducing unit vibration has been proposed in line with the conditions. Test results show that: the vibrations caused by the vapor stream excitation occurs mainly in the high-pressure rotor steam inlet end. However, the vibration signal, which occupies a large percentage of the rotor frequency of a first critical speed is sensitive to the changes in the load. Problems can be early identified, the maintenance program and maintenance means can be determined in the plant operation through analysis of vibration mechanism and sign. Security and reliability of the steam turbine running should be guaranteed. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3044